Пошаговое объяснение:
(8х+3)-(10х+6)=9
8х+3-10х-6=9
-2х-3=9
-2х=12
х=-6
14х-14=7(2х-3)+7
14х-14=14х-21+7
14х-14=14х-14
14х=14х
х=х
х=любое число
1.ответ: x=-6
2.ответ: утверждение верно для любого значения x
3.ответ: утверждение ложно для любого значения x
Пошаговое объяснение:
(8х+3)-(10х+6)=9
8х+3-10х-6=9
-2х-3=9
-2х=12
х=-6
14х-14=7(2х-3)+7
14х-14=14х-21+7
14х-14=14х-14
14х=14х
х=х
х=любое число
1.ответ: x=-6
2.ответ: утверждение верно для любого значения x
3.ответ: утверждение ложно для любого значения x